Investigating the quality of Karst water resources: A case study on Fars Namdan plain - Mohammadsadegh Talebi (Journal of Applied Research in Water and Wastewater)
One of the distinctive features of our Iran is the lack of water, which has affected the natural environment and economic-social structure. Indiscriminate exploitation of water sources and inefficient traditional irrigation systems have made the society face the challenge of water supply. Excessive extraction of underground water has caused a drop in the water level in the alluvial aquifers and caused the water resources in hard formations to be taken into consideration. Therefore, karst water sources have gained special importance in many regions in recent years. In this regard, karst water resources have gained special importance in many regions in recent years. This research was conducted with the aim is investigating the quality of water resources in the karstic formation in Fars Namdan Desert. The research data consists of meteorological, hydrological, topographic and geological maps and statistics. In this research, quantitative and qualitative parameters are identified, and then, with ArcGIS software, maps are prepared and their location is examined and analyzed. The results show that in the studied area, magnesium index is between 0.2-6.96 mg/L, sodium between 0.037-3.87 mg/L, potassium (K) between 0.01-0.049 mg/L, total hardness between 77.86-497.4 mg/L. Electrical conductivity is between 208.1-1267.1 µm/cm, pH is between 6.8-8.6, chloride is between 0.15-8.9 mg/L, sulfate is between 0.064-3.2 mg/L and bicarbonate (HCO3) is between 1.8-4.49 mg/L. So the sources of this basin have favorable conditions for drinking water.